Failure analysis of guyed transmission lines during F2 tornado event. (15th February 2015) - Hamada, A.; El Damatty, A.A.
Abstract: Motivated by many failure incidents observed worldwide of transmission line structures during tornadoes and by the lack of appropriate design procedures accounting for loads associated with such events, an extensive research program focusing on this subject initiated at The University of Western Ontario, Canada, few years ago. The current study is a part of this research program, where a numerical model that can predict the capacity and the failure mode of a transmission line system under tornadoes is developed and validated. In this numerical model, the tornado wind field is obtained from previously conducted and validated computation fluid dynamics simulations. Two different lattice transmission towers are considered for failure analysis under the developed numerical model. Due to the localized nature of tornadoes, the forces acting on a structure depends on the location of the tornado relative to the structure. As such, a parametric study is first conducted by moving the tornado in space in order to identify the critical tornado locations leading to peak forces in the tower members. Failure analysis of each system is conducted under the two most critical tornado locations identified from the parametric studies. The analysis is conducted incrementally by gradually increasing the tornado velocity till reaching the peak F2 tornado velocity. The critical velocity at which a full collapse of a tower is determined. The effects of inclusion of geometric nonlinearities and of the assumptions made regarding post yielding behavior of tension members on the failure capacity are also assessed in the study. While both transmission tower systems are shown to fail at critical velocities less than the maximum F2 tornado velocity, significant difference in those critical velocities is observed between the two considered systems.